Production of the hemagglutinin surface antigenic protei̇n of influenza a virus as a soluble form in microorganisms - TURAN, KADİR (My University, 2021)
Introduction: Influenza A viruses, which cause frequent recurring flu outbreaks in humans, are enveloped viruses and carry an eight-part single-stranded RNA genome (Husain, 2014). Influenza viral hemagglutinin (HA) and neuraminidase (NA) proteins are important for the recognition of the virus by the immune system because they are located on the viral membrane. For this reason, inactivated viruses or purified HA and NA surface antigenic proteins are used as vaccines. Both proteins are glycosylated after being synthesized in the host cells. HA proteins have a role in the attachment of the virus to the cells (Li, H. and Cao, B. 2017). In this work it was aimed is to clone the gene encoding the influenza A virus HA protein into plasmid vectors fused with other genes and to synthesize the HA protein in soluble form in Escherichia coli and Pichia pastoris.Materials and Methods: The ful- length HA (HA0) gene or a part of the gene coding HA1 domain of Influenza A/WSN/33 (H1N1) type virus was amplified with polymerase chain reaction. These fragments were fused with the sequence encoding non-variable regions of human IgG1 antibodies in an intermediate plasmid vector. The fused genes (HA0-Fc and HA1-Fc) were cloned into the plasmid vectors expressing in E. coli and P. pastoris. The resultant recombinant plasmids were transformed into E. coli and P. pastoris. The growth curves of transformants were evaluated and the recombinant proteins synthesized in the cells were analyzed with SDS-PAGE/Silver Staining.Results: For the production of recombinant protein in E. coli cells, four different vectors, carrying the T7 promoter (pET-14b-HA0-Fc and pET-14b-HA1-Fc) or the Lac promoter (pLacI-HA1-Fc and pLacI-HA0-Fc), were obtained. It was observed that the growth rate of E. coli BL21(DE3) and E. coli/Mach1 was significantly decreased after transforming with the plasmids coding HA0-Fc under the control of T7 promoter or Lac promoter. In contrast, the cells transformed with plasmids coding HA1-Fc fusion protein were grown at close rate to the control cells. SDS-PAGE/Silver staining assays showed that HA1-Fc fusion proteins were synthesized at a higher level in bacteria than that of HA0-Fc proteins. In P. pastris transformed with pPinkα-HA0.Fc and pPinkα-HA1.Fc plasmids, it was shown that the HA0.Fc and HA1.Fc fusion genes were integrated in the yeast genome by using PCR. However, the expression of the recombinant proteins was not detected with SDS-PAGE analysis.Conclusions: The result showed that the full-length viral HA proteins synthesized in cells are highly toxic to host bacteria, even when synthesized as fusion with another protein. In contrast, the HA1 domain of the HA protein can be efficiently produced in E. coli cells as fusion with human IgG1 Fc. However, it was observed that the expression system used in the study was not suitable for the recombinant production of viral HA proteins in P. pastoris cells.AcknowledgementsThis work was partially supported by a grant from The Scientific and Technological Research Council of Turkey (grant number: 112S518).and a grant from the scientific research foundation of Marmara University (grant number:SAG-C-YLP-080715-0324)
Keywords: Yaşam Bilimleri; Sağlık Bilimleri; Life Sciences; Health Sciences; Klinik Tıp (MED); Yaşam Bilimleri (LIFE); Clinical Medicine (MED); Life Sciences (LIFE)